Presentation of newly diagnosed type 1 diabetes in children and young people during COVID-19: a national UK survey. Issue 1 (2nd November 2020) - Ng, Sze May; Woodger, Katherine; Regan, Fiona; Soni, Astha; Wright, Neil; Agwu, Juliana Chizo; Williams, Eleri; Timmis, Alison; Kershaw, Melanie; Moudiotis, Christopher; Drew, Josephine
Abstract : In the UK, there have been reports of significant reductions in paediatric emergency attendances and visits to the general practitioners due to COVID-19. A national survey undertaken by the UK Association of Children's Diabetes Clinicians found that the proportion of new-onset type 1 diabetes (T1D) presenting with diabetes ketoacidosis (DKA) during this COVID-19 pandemic was higher than previously reported, and there has been an increase in presentation of severe DKA at diagnosis in children and young people under the age of 18 years. Delayed presentations of T1D have been documented in up 20% of units with reasons for delayed presentation ranging from fear of contracting COVID-19 to an inability to contact or access a medical provider for timely evaluation. Public health awareness and diabetes education should be disseminated to healthcare providers on the timeliness of referrals of children with T1D.